Loglinier Model on Immunization of Baduta - Juanda Juanda (Sciencestatistics: Journal of Statistics, Probability, and Its Application, 2024)
This study aims to analyze the relationship between the type of immunization and the province of origin of children under two years of age (BADUTA) in Indonesia in 2020. This study uses a loglinear model approach to analyze DPT-HB-Hib4 and Measles/MR2 immunization data based on gender and home province. Data was obtained from the Directorate General of Disease Prevention and Control of the Indonesian Ministry of Health. Through statistical analysis using IBM SPSS Statistics 22 software, this research found that there is a relationship between the type of immunization and the child's province of origin. The chi-square test results show that there is a significant relationship between the type of immunization and the child's province of origin. Of the several loglinear models tested, the (J, VP) model is considered the best model based on Goodness-of-fit criteria. Thus, this study concludes that there is a relationship between the type of immunization and the province of origin of children under two years old in Indonesia in 2020.